Hubungan tangibles, realibility, responsiveness, assurance, dan empathy terhadap kepuasan pasien kemoterapi di Rumah Sakit X di Kabupaten Semarang - Susi Purwitasari; Chriswardani Suryawati; Cahya Tri Purnami (Holistik Jurnal Kesehatan, 2023)
Background: The hospital is a health service institution that provides comprehensive individual health services that provide inpatient, outpatient, and emergency services. Chemotherapy is a cancer therapy using cytostatic drugs that are inserted into the body through the intravenous or oral route with long maintenance therapy and intensive therapy periods. The quality or quality of health services can be seen from several perspectives, namely the perspective of health service providers, the perspective of funders, the perspective of owners of health service facilities, and the perspective of patients. The tangibles aspect in service is a physical aspect that can support existing services at the Hospital and the empathy aspect of service is an assessment of service quality as seen from the empathy of employees in providing services.Purpose: To determine the relationship between the quality of chemotherapy services and patient satisfaction at Ken Saras Ungaran Hospital.Method: Quantitative with cross sectional approach. The population in this study were chemotherapy inpatients at Ken Saras Ungaran Hospital from February to March 2023 with a total of 135 patients being treated. Sampling with purposive sampling technique.Results: The tangibles variable has a positive relationship with value (r = 0.486, p <0.000). Reliability has a positive relationship with value (r = 0.460, p < 0.000). Responsiveness has a positive relationship (r = 0.492, p <0.000). Assurance has a positive relationship with value (r = 0.626, p < 0.000), and empathy has a positive relationship with value (r = 0.548, p < 0.000).Conclusion: There is a significant relationship between tangibles, reliability, responsiveness, assurance, and empathy in patient satisfaction at Ken Saras Ungaran Hospital.Keywords: Hospital; Service Quality; ChemotherapyPendahuluan: Rumah Sakit merupakan institusi pelayanan kesehatan yang menyelenggarakan pelayanan kesehatan perorangan secara paripurna yang menyediakan pelayanan rawat inap, rawat jalan, dan gawat darurat. Kemoterapi adalah terapi kanker dengan menggunakan obat-obatan sitostatik yang dimasukkan ke dalam tubuh melalui intra vena atau oral dengan terapi pemeliharaan yang cukup panjang dan periode terapi yang Intensif. Kualitas atau mutu layanan kesehatan dapat dilihat dari beberapa perspektif yaitu perspektif pemberi layanan kesehatan, perspektif penyandang dana, perspektif pemilik sarana layanan kesehatan dan perspektif pasien. Aspek tangibles dalam pelayanan merupakan aspek fisik yang dapat menunjang dalam pelayanan yang ada di Rumah Sakit dan Aspek empathy dalam pelayanan merupakan penilaian kualitas pelayanan yang dilihat dari empati karyawan dalam memberikan pelayanan.Tujuan: Untuk menganalisis hubungan kualitas pelayanan kemoterapi terhadap kepuasan pasien di Rumah Sakit Ken Saras Ungaran.Metode: Kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah pasien rawat inap kemoterapi di Rumah Sakit Ken Saras Ungaran pada Februari sampai maret 2023 dengan jumlah pasien yang dirawat tercatat 135 pasien. Pengambilan sampel dengan teknik proposive sampling.Hasil: Variabel tangibles memiliki hubungan positif dengan nilai (r = 0.486, p < 0.000). Realibility memiliki hubungan positif dengan nilai (r = 0.460, p < 0.000). Responsiveness memiliki hubungan positif dengan (r = 0.492, p < 0.000). Assurance memiliki hubungan positif dengan nilai (r = 0.626, p < 0.000). Empathy memiliki hubungan positif dengan nilai (r = 0.548, p < 0.000).Simpulan:  Adanya hubungan yang signifikan antara tangibles, reliability, responsiveness, assurance, dan empathy terhadap kepuasan pasien rawat inap di Rumah Sakit Ken Saras Ungaran.